A STUDY ON THE SECOND YEAR STUDENTS’ READING ABILITY OF SMK NEGERI 3 PEKANBARU - Gultom, Yuli Noviyanti; Novitri, Novitri; Ras, Fakhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this study was to find out the second year students’ ability level of SMKN 3 Pekanbaru in reading comprehension. The design of the study is quantitative research paradigm. The population of this research were all the second year students of SMKN 3 Pekanbaru divided into 5 majors ; Hotel Accommodation, Culinary Art, Patisserie, Design Fashion and Beauty Class. The total number of the population were 266 students. In order to choose the sample and try out class, the lottery was taken. Culinary Art 1 was determined as the try out class while Culinary Art 2 as the sample class which both of the classes consist of 34 students. To identify the students’ reading ability, the reading test was administered. Before conducting the test, a try out was done in order to determine the reliability and validity of the test. The data were collected by administering a reading test to the students in the form of multiple choice. The result shows that the ability of the second year students in reading comprehension was classified into good level with the mean score of 70.53. There are three of reading components that can be classified into excellent (finding factual information, finding main ideas, and the meaning of vocabularies words). The other components are categorized into good level (finding references, finding inferences, and finding social functions. The other two components can be said as average level (identifying language features and identifying generic structures). The implication of the findings is that the second year students of SMKN 3 Pekanbaru should be well trained in aspects of language features and generic structures.Key Words: Ability, Reading